Feelings and expectations of mothers of newborns in a neonatal intensive care unit - Melo, Celia Regina Maganha; Villa, Solange Galan; Silvério, Natália Fanelli; Santana, Renata Alves (Revista de Enfermagem UFPE on line, 2010)
<span style="font-family: ";Trebuchet MS";,";sans-serif";; font-size: 10pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: ES-TRAD; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="ES-TRAD"> ABSTRACT Objective: to know the feelings and expectations of mothers of newborns in a neonatal intensive care unit. Method: a descriptive study with quantitative approach. The sample consisted of 13 mothers who had their infant in NICU, in June and July 2008. The instrument was a form; the first part with questions related to the mothers’ characterization and the second part containing variables of the study, with objective questions and multiple choice answers. The project was approved by the Research Ethics Committee of the University of the Sacred Heart under the protocol nr. 49/08. Results: most of the mothers were married young adults, had social security number, living in Bauru city, São Paulo, Brazil. Regarding the reaction to hospitalization, 77% were anxious and distressed, 61% were concerned at the moment of the interview, 38.5% felt comfortable and calm in the hospital, 84.5% reported that the mother/nursing staff was good, 77% said that there was a change in their daily life. Conclusion: the mothers showed feelings of worry, anxiety, calmness and hope. The majority believed that their child would leave soon from the NICU and that treatment would be effective, thus showing a relationship of trust with the team that assisted their newborn. Descriptors: mother; neonatal icu; nursing; neonatal nursing; newborn; nursing care; hospital care. RESUMO Objetivo: conhecer os sentimentos e expectativas de mães de recém nascidos em uma Unidade de Terapia Intensiva Neonatal. Método: estudo descritivo com abordagem quantitativa. A amostra foi constituída por 13 mães que tinham seu bebê internado na UTIN, nos meses de junho e julho de 2008. O instrumento foi um formulário, sendo a primeira parte com perguntas relacionadas à caracterização das mães e a segunda contendo as variáveis em estudo, com perguntas objetivas e respostas de múltipla escolha. O projeto foi aprovado pelo Comitê de Ética em Pesquisa da Universidade do Sagrado Coração, protocolo n. 49/08. Resultados: observou-se que a maioria das mães eram jovens adultas casadas, tinham registro em carteira de trabalho, residiam em Bauru/SP. Sobre a reação à internação, 77% ficaram preocupadas e angustiadas; 61% estavam preocupadas no momento da entrevista; 38,5% sentiam-se acolhidas e calmas no ambiente hospitalar; 84,5% referiram que o relacionamento mãe/equipe de enfermagem era bom; 77% disseram que houve mudança no seu dia a dia. Conclusão: as mães evidenciaram sentimentos de preocupação, angústia, calma e esperança. A maioria acreditava que seu bebe sairia logo da UTINN e que o tratamento seria eficaz, demonstrando uma relação de confiança com a equipe que prestava assistência ao seu filho. Descritores: mãe; uti neonatal; enfermagem; enfermagem neonatal, recém-nascido; cuidados de enfermagem; assistência hospitalar. RESUMEN Objetivo: conocer los sentimientos y expectativas de las madres de los recién nacidos en una unidad de cuidados intensivos neonatal. Método: estudio descriptivo, con enfoque cuantitativo. La muestra estuvo constituida por 13 madres que habían tenido su bebé en el hospital UCIN en los meses de junio y julio de 2008. El instrumento fue un formulario; la primera parte, constituyó de cuestiones relacionadas con la caracterización de las madres y la segunda parte, con las variables en estudio, con preguntas objetivas y respuestas de elección múltiple. El proyecto fue aprobado por el Comité de Ética en Pesquisa de la Universidad del Sagrado Corazón, bajo el Protocolo de 49/08. Resultados: se observó que la mayoría de las madres eran adultos jóvenes casadas, tenían cartera de trabajo y viven en Bauru/SP. En cuanto la reacción a la hospitalización, 77% estaban ansiosas y angustiadas, 61% estaban preocupadas en el momento de la entrevista, y 38,5% sentían se bienvenidas y tranquilas en el hospital, 84,5% informó de el relacionamiento madre/ equipo de enfermería era bueno, 77% dijo que hubo cambio en el día a día. Conclusión: las madres demostraron sentimientos de preocupación, ansiedad, calma y esperanza. La mayoría acreditaba que su bebé volvería pronto de la UTIN y que el tratamiento sería eficaz, lo que muestra una relación de confianza con el equipo que trató a su hijo. Descriptores: madre; uci neonatal; enfermería; enfermería neonatal; recién-nascido; atencíon de enfermería; atención hospitalaria.